Combined Oral Contraceptives for Polycystic Ovary Syndrome: Pro and Contra (Review) - I. A. Mazerkina; I. G. Davydov; O. S. Alyautdina (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
INTRODUCTION. Polycystic ovary syndrome (PCOS) is the main cause of female infertility. Clinical practice guidelines on PCOS recommend combined oral contraceptives (COCs) as first-line therapy. Given the association of PCOS with a number of clinical conditions, including obesity, type 2 diabetes mellitus, metabolic syndrome, anxiety and depressive disorders, an increased risk of endometrial cancer, and cardiovascular diseases, it is important to describe and systematise data on the benefits and risks associated with COCs.AIM. This study aimed to review current data on the use of COCs in PCOS, focusing on the rationality of prescribing, the main risks of using COCs, and the measures to minimise these risks.DISCUSSION. Hirsutism is the most prominent clinical manifestation of hyperandrogenism; in PCOS, its prevalence is 65-75%. COCs containing progestins with anti-androgenic properties are effective in treating hirsutism and superior to anti-androgens alone. Women with PCOS are at increased risk of endometrial cancer due to prolongation of the oestrogen-dependent proliferative phase. This risk can be mitigated by the normalising effect of COCs on the menstrual cycle and the effect of the progestin component of COCs. This review highlights the controversial nature of data on the association of COCs with emerging or exacerbating mental disorders, impaired glucose tolerance, and arterial hypertension/other cardiovascular risks in PCOS. Since the main safety issue with COCs is their thrombogenicity, clinicians should take special care when prescribing medicinal products from this group to PCOS patients. Data on the effect of COCs on fertility in women with PCOS are limited, but there is published evidence of an adverse effect of long-term use of COCs on the results of assisted reproductive technologies.CONCLUSIONS. The key benefit of the non-contraceptive use of COCs in PCOS is in treating hyperandrogenism, mainly hirsutism. To achieve effect, the patient should take COCs containing progestins with anti-androgenic properties for at least 6 months. PCOS patients can also use COCs for contraception. Clinicians prescribing COCs to women with PCOS should consider the individual patient context, the aim of treatment, and any potential risks associated with COCs.